2021
DOI: 10.3390/rel12100845
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for the Development of the Activity of the Catholic Church in Poland in the Field of Social Communication

Abstract: In recent years, the Catholic Church has been forced to change its attitude towards social communication and mass media. It has had to face not only religious but image challenges. Worldview matters, contemporary problems regarding the institution of marriage or pedophilia in the Church are constantly being debated in mass media, thus creating dangers in terms of critical public reception. This situation has also been occurring in Poland in recent years. The observed progress regarding opening the Church to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…In any case, it would be interesting for researchers, as well as churches, to see if and which media sources, in general, young people pay attention to and how regularly. Today, the media serves several purposes, from education, upbringing, and entertainment to manipulation, abuse, and harm (Gawro ński et al 2021), and surely it does not distribute religious-life-related information. The media saturation of our society has an impact on the young generation, sometimes tracked by the time young people spend in the presence of media content (Kobylarek 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In any case, it would be interesting for researchers, as well as churches, to see if and which media sources, in general, young people pay attention to and how regularly. Today, the media serves several purposes, from education, upbringing, and entertainment to manipulation, abuse, and harm (Gawro ński et al 2021), and surely it does not distribute religious-life-related information. The media saturation of our society has an impact on the young generation, sometimes tracked by the time young people spend in the presence of media content (Kobylarek 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Based on their fair literature analysis and interpretation, the authors found that in recent years persistent critical opinions towards the Catholic Church appeared. This suggests that the Church in Poland has been losing confidence in its image, probably due to inefficient communication [ 23 ]. Attending Catholic school and being a practicing believer influenced some aspects of faith and family relations during the pandemic, but in most aspects, they did not influence attitudes toward health issues.…”
Section: Discussionmentioning
confidence: 99%
“…5: Merchandising de la promoción IV. DISCUSIONES La Iglesia Católica de Trujillo, actualmente se encuentra administrada por el Arzobispado Metropolitano de Trujillo, se considera que la principal fortaleza con la que cuenta es su permanencia en el mercado, lo cual le ha permitido establecer una fuerte marca e imagen [3]; no obstante se encuentra también una debilidad muy latente en la actualidad, los problemas organizacionales que generaron una mala imagen y opiniones negativas por parte de la población han generad o una disminución de la feligresía total a nivel nacional y local [6].…”
Section: E F M a M J J A S O N Dunclassified
“…Actualmente la Iglesia Católica se ve afectada por diversas acusaciones, lo cual ha influido en su imagen frente a los feligreses y el mundo, es por ello que ha iniciado el uso de mejorar su imagen [6].…”
Section: Introductionunclassified